Enhancing EFL Students’ Recount Writing through Animation Movies - Diki, Diki Masria; Supriadi, Adi (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama’ah, 2026)
Study purpose. This study aims to analyze the implementation of animation movies in improving EFL students’ recount writing skills. Materials and Methods. This study employed a Classroom Action Research (CAR) approach conducted in two cycles, consisting of planning, acting, observing, and reflecting stages. Data were collected through writing tests, observations, and documentation, and were analyzed using descriptive qualitative methods to examine students’ writing improvement. Results. The findings revealed a significant improvement in students’ writing ability, as reflected in their enhanced capacity to develop ideas, organize texts more coherently, and use more appropriate vocabulary and grammatical structures, particularly in the use of past tense. In addition, the use of animation movies successfully increased students’ engagement and motivation, making the learning process more active and meaningful. Conclusion. The study concludes that animation movies are effective in improving students’ recount writing skills while also promoting their active engagement in the learning process.